Three new Sisyphus species (Coleoptera: Scarabaeidae: Scarabaeinae) from shaded vegetation in southern Africa - Daniel, Gimo M.; Davis, Adrian Lv.; Scholtz, Clarke H. (Zootaxa, 2016)
Descriptions are provided for three new shade-associated species in the dung beetle genus, Sisyphus Latreille, 1807: Sisyphus umbraphilus sp. nov., Sisyphus oralensis sp. nov., and Sisyphus neobornemisszanus sp. nov. All three species are illustrated by photographs of habitus, diagnostic features, and male aedeagi. A map is provided showing their geographical distributions.